2014
DOI: 10.3109/09513590.2014.892066
|View full text |Cite
|
Sign up to set email alerts
|

The rate of high ovarian response in women identified at risk by a high serum AMH level is influenced by the type of gonadotropin

Abstract: The aim was to compare ovarian response and clinical outcome of potential high-responders after stimulation with highly purified menotropin (HP-hMG) or recombinant follicle-stimulating hormone (rFSH) for in vitro fertilisation/intracytoplasmic sperm injection. Retrospective analysis was performed on data collected in two randomized controlled trials, one conducted following a long GnRH agonist protocol and the other with an antagonist protocol. Potential high-responders (n = 155 and n = 188 in the agonist and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…The two markers are strongly related to the quantitative aspect of ovarian reserve; hence a low AMH and/or AFC are highly indicative of possible low number of growing follicles and oocyte following ovarian stimulation. Moreover, both low AMH and AFC have been associated to reduced pregnancy and live birth following IVF independent of age [35][36][37][38][39][40][41]. This may indicate some relationship between quantity and quality of oocytes, with a The present study because of its retrospective design has relevant limitations, including a biased selection of women recruited for the study.…”
Section: Discussionmentioning
confidence: 85%
“…The two markers are strongly related to the quantitative aspect of ovarian reserve; hence a low AMH and/or AFC are highly indicative of possible low number of growing follicles and oocyte following ovarian stimulation. Moreover, both low AMH and AFC have been associated to reduced pregnancy and live birth following IVF independent of age [35][36][37][38][39][40][41]. This may indicate some relationship between quantity and quality of oocytes, with a The present study because of its retrospective design has relevant limitations, including a biased selection of women recruited for the study.…”
Section: Discussionmentioning
confidence: 85%
“…The risk for OHSS may be reduced in women with high AMH levels who receive lower doses of gonadotropins for shorter periods (a mild stimulation protocol) (Anckaert et al, 2012;Nelson et al, 2007). Thus, the choice of an antagonist-controlled protocol (with mild stimulation doses) may minimize the frequency of cycle cancellations caused by OHSS in women with high AMH levels (Arce et al, 2014;Casano et al, 2012;Fauser et al, 2010;Hamdine et al, 2014;Nelson et al, 2007). Additionally, a recent analysis of two prospective, randomized trials comprising over 1400 assisted reproduction technique cycles indicated that selection of gonadotrophin, i.e.…”
Section: Amh: the Evidence As A Predictive Methodsmentioning
confidence: 97%
“…Moreover, AMH has been identified as one of the best predictor of ovarian response in women undergoing ovarian stimulation with corifollitropin alfa in a GnRH antagonist protocol [16]. There is evidence that the type of gonadotropin may affect certain patients such as women at high risk of hyper-response or with PCOS [15,17].Our results indicate that the IVF protocol utilized is effective in terms of both clinical procedures and embryological parameters. The number of oocytes retrieved was regular as well as the maturity of the cells and the fertilization rate, suggesting the suitability of ovarian stimulation and ovulation induction.…”
mentioning
confidence: 60%
“…High basal concentrations of AMH have been associated with hyperresponse to gonadotropin stimulation [15]. Moreover, AMH has been identified as one of the best predictor of ovarian response in women undergoing ovarian stimulation with corifollitropin alfa in a GnRH antagonist protocol [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation